A syntactical analysis of sentence structures and types in the song lyrics of “To The Bone” and “Lathi” - Muhammad Ilmi Al Bahy; Ruly Indra Darmawan (Universitas Negeri Semarang, 2025)
This study aims to analyze the sentence structures and types found in two popular Indonesian songs written in English, “To the Bone” by Pamungkas and “Lathi” by Weird Genius ft. Sara Fajira, and to examine how the songwriters’ syntactic choices contribute to the song lyrics’ expressive impact. Using Carnie’s phrase structure rules (PSRs) for tree diagram constructions, the study identifies constituents, categories, and grammatical functions in the lyrics written by non-native English speakers, especially Indonesians. The results show that simple declarative sentences appear most frequently, with “To The Bone” containing 15 simple sentences within 39 declaratives and “Lathi” containing 9 simple sentences within 22 declaratives. Such syntactic patterns are commonly chosen for emotional clarity and accessibility. On the other hand, “To the Bone” also uses imperatives and interrogatives to enhance emotional engagement, whereas “Lathi” exclusively uses declaratives. Lastly, these songs use fragments and interjections to create emotional impact and support rhythmic flow. In conclusion, these results outline how non-native songwriters manipulate English syntax to create clear narratives and evoke strong emotions in the song lyrics.